2023
DOI: 10.1007/jhep01(2023)145
|View full text |Cite
|
Sign up to set email alerts
|

Search for lepton flavor violating decay at FASER

Abstract: FASER is one of the promising experiments which search for long-lived particles beyond the Standard Model. In this paper, we consider charged lepton flavor violation (CLFV) via a light and weakly interacting boson and discuss the detectability by FASER. We focus on four types of CLFV interactions, i.e., the scalar-, pseudoscalar-, vector-, and dipole-type interaction, and calculate the sensitivity of FASER to each CLFV interaction. We show that, with the setup of FASER2, a wide region of the parameter space ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…Using a large number of the dark Higgs bosons produced by heavy meson decays through the scalar mixing with the SM Higgs boson, it was shown that the sensitivity to the dark photon parameters can be enlarged. The similar analyses have been studied for inelastic dark matter [19], lepton flavor violation [12], dark Higgs [13,20,21] in gauge L µ − L τ [22] and B − L models [23]. In these studies, only decay of the on-shell dark Higgs was considered.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a large number of the dark Higgs bosons produced by heavy meson decays through the scalar mixing with the SM Higgs boson, it was shown that the sensitivity to the dark photon parameters can be enlarged. The similar analyses have been studied for inelastic dark matter [19], lepton flavor violation [12], dark Higgs [13,20,21] in gauge L µ − L τ [22] and B − L models [23]. In these studies, only decay of the on-shell dark Higgs was considered.…”
Section: Introductionmentioning
confidence: 99%
“…In refs. [11][12][13][14], the dark photon production from the dark Higgs decay at the FASER and other experiments [15][16][17][18] was studied. Using a large number of the dark Higgs bosons produced by heavy meson decays through the scalar mixing with the SM Higgs boson, it was shown that the sensitivity to the dark photon parameters can be enlarged.…”
Section: Introductionmentioning
confidence: 99%